Association between self-efficacy and health-related quality of life in patients with systemic lupus erythematosus - Zeña Huancas, Paola Alejandra (2019)
Background: Self-efficacy for managing chronic conditions assesses the confidence a person has on the ability of successfully perform specific tasks related to a chronic condition in several different situations. Self-efficacy is considered one of the most important modifiable factors in educational interventions that enhance Systemic Lupus Erythematosus (SLE) patients’ mental health status. Low disease self-efficacy is associated with SLE morbidity. Objectives: To determine the association of several domains of self-efficacy for managing chronic conditions and health-related quality of life (HRQoL) in SLE patients.